The Relationship Between Transformational and Transactional Leadership Style with the Employees' Job Satisfaction - Fakhrossadat Nnasiri; Ali emadi (مطالعات مدیریت بهبود و تحول, 2016)
The purpose of this research was to investigate the relationship between transformational and transactional leadership style among the employees' job satisfaction in the Directorate General of Telecommunication in the province of Hamedan.Research methodology is descriptive and the correlation of structural is equation modeling. Counted community includes all the employees and according to Kregecie and Morgan chart and using classical random sampling is collected from 220 (114 females and 106 males) employees. Two questionnaires were used for data collection, including1. Questionnaire Bass and Olive leadership style and 2.job satisfaction. To obtain validity and content validity formal methods were used. Cronbach's alpha reliability coefficient is calculated through the order for job satisfaction/088, Transformational style/086and transactional Leadership Style /091 respectively. Data were analyzed by descriptive statistics, Pearson correlation coefficient, and t-test for independent groups, ANOVA and stepwise regression. The data collected were analyzed using statistical SPSS.Results show: The application of transformational leadership style is above average, but a transactional leadership style and employees' job satisfaction rate are moderate. There are significant positive correlations between transformational leadership and job satisfaction, but there are not significant positive between transactional leadership and job satisfaction